Analisis Dampak Penerimaan Kas Non-Tunai (Cashless) Pada Pengendalian Transaksi Di Prama Sanur Beach Hotel Melalui Analisis SWOT - I Nengah Darmawan Arta Darmika; Ni Komang Sumadi; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2026)
The purpose of this study is to analyze cashless cash receipts at Prama Sanur Hotel Bali through cashless payments and discuss how the cashless payment process works, and its impact on transaction recording. This research was conducted based on the phenomenon of the greater presence of cashless payment users and the increase in users of cashless payment systems over the past 2 years, namely 2023-2024. In conducting the analysis, researchers used a SWOT analysis consisting of Strengths, Weaknesses, Opportunities, and Threats. The data collection technique used was interviews with Cashier Outlets, Accounts Receivable and Income Auditors. The results of this study found that the types of instruments available at Prama Sanur Beach Hotel are card-based payment instruments (credit cards, debit cards) and QRIS. Cashless cash receipts are supported by card slip documents, guest bills, cashier worksheets, gross income reports, daily bank reconciliation reports, credit card payment summaries. Accepting cashless payments through non-cash payments has the advantage of facilitating transaction monitoring, helping to record transactions more quickly and accurately, and reducing the risk of incidents. The downside of this method is the EDC machine and human error, which can cause discrepancies between recorded transactions and the money received at the bank. This method offers the opportunity to increase guest promotions, with banks offering special rates for admin fees and also providing rewards to hotels to reduce the burden borne by the hotel. Furthermore, the threat of accepting cashless payments through non-cash payments is problematic internet signals and ensuring guest trust in the use of non-cash payment methods, especially QRIS.